Genomically Selected Genes Associated with a High Rate of Egg Production in Puan Panjiang Black-Bone Chickens - Xiaomeng Miao; Zhiying Huang; Jia Liu; Li Zhang; Yulong Feng; Yalan Zhang; Diyan Li; Zhonghua Ning (Animals)
Puan Panjiang black-bone chickens are renowned for their distinctive traits, deep black coloration, and high-quality protein content, making them a focus of genetic research due to their unique egg-laying abilities. In this study, 110 Puan Panjiang black-bone chickens were used to investigate the effects of natural and artificial selection influencing egg production. Whole-genome resequencing data from red junglefowl (RJF) and high-egg-production (HEP) and low-egg-production (LEP) groups of Puan Panjiang black-bone chickens revealed significant genetic variants associated with egg production traits. Additionally, transcriptome analysis of 47 samples from ovary stroma, small white follicles (SWFs), small yellow follicles (SYFs), and liver tissues from 6 HEP and 6 LEP groups identified differentially expressed genes. Notably, differences in egg production were linked to small yellow follicles rather than ovary stroma or SWFs. Key candidate genes, including TRIM7, CASR, SPTBN5, GAL1, ZP1, IL4I1, and CCL19, were identified as potential contributors to egg-laying performance. This study underscores the genetic diversity within this breed and provides valuable insights for future breeding programs to enhance egg production, supporting the sustainable development of this local resource.